A simulation study on how to optimally store products in a warehouse of a fashion supply chain selling through an e-commerce channel. (5th October 2022) - Bottani, Eleonora; Tebaldi, Letizia; Rossi, Mariachiara; Casella, Giorgia
Where is it convenient the most to allocate a determined product? This paper, by means of a simulation tool, makes an attempt to answer this question, for the specific case of an e-commerce warehouse in which fashion items are stored. According to the typical steps of the Deming cycle, after having studied the current situation (AS IS scenario) of items allocation, a simulated one (TO BE scenario) was developed for studying a new allocation strategy, and for its assessment four key performance indicators were considered: the storage and picking productivity (both expressed in terms of processed units per hour), the % of FIFO batch for multi-customer orders and the time spent for batching (measured in hours). Results from the implementation show an improvement of the KPIs under investigation, as well as the observation of the specific targets set, and consequently an optimisation of picking activities.